ICTs and Second Language Learning - Musskopf, Ângela; Nice Ferrari Barbosa, Débora; B. Scherer Bassani, Patrícia (RENOTE, 2018)
The present article aims to show the practices mediated by the use of educational digital resources developed with undergraduate students, which used three digital resources related to writing skills: a MOOC, the Text Inspector, and the Write and Improve. Furthermore, important discussions are made about the theories of Second Learning Acquisition and it’s teaching methodologies, highlighting the approaches using online educational resources. The results of the practices show that the undergraduate students saw improvement in their developed skills, which indicates that the use of technological resources can contribute to the process of learning.